America The Janus Nation - Murphy, Peter (Budhi: a Journal of Ideas and Culture, 2022)
America is a paradoxical society. That is one of its strengths. One of its weaknesses is its periodic inability to understand its own paradoxical nature. It is a Janus nation, one in which (in principle) incompatible things exists in a simultaneous state. When this paradoxical fusion works, it has great benefits. When it fails to work, American society loses its inner equilibrium. Pugnacious antagonisms arise in its place. The tension within the United States between the drive toward a union of opposites (mostly famously embodied in its Constitution) and the periodic centrifugal spinning out of American society into a state of mutual loathing is discussed - most recently the case of the 2010s and the rise of ultra-partisan hyperbole.